Molecular epidemiology of Bartonella quintana endocarditis in patients from Israel and Eastern Africa - Sato, Shingo; Shapira, Lev; Tasher, Diana; Maruyama, Soichi; Giladi, Michael (BMC infectious diseases, 2023)
Bartonella quintana is an important cause of culture-negative endocarditis. Although humans have been considered as its only reservoir, recent studies showed that macaque species are also reservoirs of B. quintana. Based on multi-locus sequence typing (MLST) B. quintana strains have been classified into 22 sequence types (STs), with 7 STs exclusively found in humans. Data regarding the molecular epidemiology of B. quintana endocarditis is limited to only 3 STs identified in 4 patients from Europe and Australia. We studied B. quintana endocarditis acquired in Eastern Africa or Israel to investigate the genetic diversity and clinical relatedness of B. quintana from distinct geographic regions. Eleven patients with B. quintana endocarditis, 6 from Eastern Africa and 5 from Israel, were studied. DNA was extracted from cardiac tissue or blood specimens and analyzed by MLST based on 9 genetic loci. An evolutionary relationship between STs was visualized by a minimum spanning tree. A phylogenetic tree was constructed with the concatenated sequences (4271 bp) of the 9 loci using the maximum-likelihood method. Six strains were classified into previously described STs while 5 strains were identified for the first time and classified into new STs 23-27 which clustered with the previously reported STs 1-7 from human strains found in Australia, France, Germany, the USA, Russia, and the former Yugoslavia, without indication of geographical structuring. ST2 was the most prevalent ST, found in 5 of 15 patients with endocarditis (33.3%). ST26 appears to be a primary founder of the human lineage. The new and previously reported human STs form a single human lineage, clearly separated from the other 3 B. quintana lineages of cynomolgus, rhesus, and Japanese macaques. From evolutionary perspectives, these findings support the assumption that B. quintana has co-evolved with host species to form a host-speciation pattern. ST26 is suggested herein as a primary founder of the human lineage and may be key to explore where B. quintana had first originated; ST2 is a dominant genetic type associated with B. quintana endocarditis. To confirm these findings, additional worldwide molecular epidemiological studies are required.